THE SHORT- TERM CORONAVIRUS (COVID-19) PANDEMIC EFFECT: AN EMPIRICAL INVESTIGATION OF INDIAN STOCK MARKET (BSE) - Afzal, Mohd Atif; Khan, Nasreen; Mohammad, Abdul Saboor; Taqi, Mohd (Indian Journal of Finance and Banking, 2022)
India’s precautionary step toward COVID-19 led to 1.3 billion people enduring lockdown, consequently halting the wheels of the Indian economy. Though the crash of the stock market was evident and explanatory, it left all stakeholders (including the investors and government) with no choice. Deteriorating SENSEX and other indices forced investors to withdraw and lose attraction from the market and looped in more serious issues to the Indian stock market. This paper empirically analyses the short-term impact of COVID-19 on five selected BSE indices for SENSEX, FMCG, Bank, Corporate-Bond, and Industrial using econometric models. Stationarity was checked by Augmented Dickey-Fuller and Philips-Perron test. Autocorrelation was assessed and mitigated by Durbin-Watson, Breusch-Godfrey Serial Correlation LM test, and Cochrane-Orcutt transformation method. This study attempts to apply Multiple Regression, the GARCH model, Standard Vector Autoregression (S-VAR), and Impulse Response Function (IRF) to decode the relation. The results indicated that the COVID-19 pandemic is adversely affecting the performance of the Indian stock market in the short run. All the indices showed a negative relationship antecedent with the effect of COVID-19, except for the SPICBI index. This paper implies investment solutions for the investors and policymakers to cope with the unprecedented situation amidst COVID-19. JEL Classification Codes: H54, R53.